Improving biology students' concept understanding and media literacy skills through authentic text hierarchical cognitive instruction - Serrana, Venia C.; Yangco, Rosanelia T.; Zara, Nerissa O.; Paderna, Edwehna Elinore S. (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study investigated the effects of authentic text hierarchical cognitive instruction on the students' concept understanding and media literacy skills in a biology course called Anatomy and Physiology. Furthermore, it determined whether students' multiple intelligences modify the effects of authentic texts on concept understanding and media literacy skills. It also sought to find out if there is a correlation between concept understanding and media literacy skills. The intervention group received instructions aided by authentic texts such as comics, advertisements, song, poem, poster, video, food label, lab result, movie, and children's book. The conventional group was exposed to the lecture method of instruction without the aid of authentic text materials. Both groups took the pretests and posttests in Anatomy and Physiology Concept Understanding Inventory (APCUI) and Media Literacy Skills Inventory (MLSI). Only the intervention group took the Multiple Intelligence (MI) Inventory Test. Qualitative results from focus group discussion were used to support the quantitative data. Findings show that authentic text hierarchical cognitive instruction significantly improved concept understanding of students. It also significantly improved media literacy skills especially the evaluate and create aspects. Furthermore, learners' type of intelligences does not affect concept understanding nor media literacy skills, such that regardless of the students' type of intelligence, concept understanding in Anatomy and Physiology and media literacy skills improved when exposed to authentic text instruction. It was also found that concept understanding and media literacy skills are two independent and unrelated concepts. It is therefore recommended that authentic text hierarchical cognitive instruction be considered in teaching Biology and other science subjects.
Thesis
Includes bibliographical references
Keywords: Biology -- Study and teaching (Higher) -- Philippines -- Quezon City; Anatomy -- Study and teaching (Higher) -- Audio-visual aids; Physiology -- Study and teaching (Higher) -- Audio-visual aids; Media literacy -- Philippines -- Quezon City